Simple Model for the Spreading of Inks in Bioprinting—Revealing Relevant Scaling Laws—Part I Theory - Schubert, Dirk W. (Macromolecular Theory and Simulations, 2021)
A model taking into consideration viscosity and evaporation is suggested to describe the spreading kinetics of struts in bioprinting. Scenarios resulting by complete and partial wetting are discussed and described. Applicable fit functions and predictive scaling laws are given, relating viscosity of bioinks, process parameters such as print speed and throughput to the strut width. The approach is primarily based on 1D spreading.
Created from Fastlane, Scopus look-up
Keywords: 3D printing; bioprinting; scaling laws; shape fidelity; strut spreading; viscosity